A Study on Female Victims of Burn Injury at Rims, Ranchi, Jharkhand - Lishu Chaure; Nawal Kumar Singh; Kumar Shubhendu; Tulsi Mahto; Ajit Kumar Chaudhary (Institute of Medico-legal Publications Pvt Ltd, 2021)
Burn injury is one of the most common cause of unnatural deaths worldwide. While survival after occurrenceof burn injury has drastically increased in past decades especially in developed countries like India, burninjury continues to be a common cause of unnatural deaths. Though both males and females may be victimsof burn, females are more susceptible as they are more involved in household activities .Often the mannerof burn is closed in mystery and unreliable statements. The reason behind this action may be domestic,personal, occupational or social tragedy and more recently dowry deaths. Burns in married female wheredeath of female occurs below 30 years and within seven years of her marriage. Such death cases are tobe investigated by Magistrate under CrPC 176 and other female burn and male burn deaths are routinelyinvestigated by police as per section 174 CrPC.